Modification of TiO2 with clam-shell powder for photodegradation of methylene blue - Ling, M.F.C. (Springer, 2022)
The wide application of dyes has become the motivation of this research as significant amount of methylene blue (MB) in water portrayed potential risk to human well-being. Photocatalytic process is a promising yet sustainable method for the removal of dyes. In this study, clam shell (CS) powder has been successfully loaded into TiO2 through hydrothermal method resulting in TiO2/Clam Shell powder composite (TiO2/CS) to improve the photodegradation performance of TiO2. The produced composites exhibit lower bandgap energy, larger surface area and high crystallinity. It is observed that TiO2/CS ratio of 4:1 is the optimum amount of CS in composite to obtain the most effective photodegradation process. Under Xenon lamp irradiation, TiO2/CS 4:1 composite has completely degraded 10 ppm of MB within 120 mins with removal rate constant of 0.0251 minâ1. The loading of CS has enhanced the visible light absorption through lowering the bandgap energy of TiO2 from 3.0 to 2.2 eV and increases specific surface area of TiO2. The excellent performance of TiO2 composite is attributed to synergistic effect of CS loading in TiO2, which acted as support and electron trapper. Subsequently, the composite also portrayed good stability even after three cycles of degradation with 94.09 removal. The combination of CS and TiO2 shown improved photodegradation which signified its potential to be applied in water treatment. Figure not available: see fulltext. Â© 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.